Task Shifting in Growth Monitoring: Mother/ Caregivers roles at the Health Facilities - Opeyemi, Oladunni; Oladimeji, Oladepo (International Journal of Global Health, 2022)
Growth monitoring activities has been seen as the most effective ways to identify malnutrition and promotes early child development. This has been linked with long term health and social benefits for the child, family and the community. Over the years, the growth monitoring activities have centred round the health workers. Therefore, the study explored task shifting on Mother/ Caregivers capability to undertake growth monitoring roles at the health Facilities in Oyo State Nigeria. Qualitative methods using focused group discussion and Key informant interview guide were used for data collection among 6-8 groups of 10 mothers and 20 health workers providing the service. The data was analysed using inductive coding to generate the themes. The study showed mothers/caregivers low knowledge on growth monitoring and health workers documented some potential challenges encounter during the activities. The mothers/caregivers show low knowledge on growth monitoring. Therefore, mothers/caregivers were willing to take up the role.
Keywords: Growth Monitoring; task shifting; health workers; mothers/caregivers